Design and Analysis of Fractional PID Controller for Isolated Bidirectional DC-DC Converter - C. Ramya, K.; Vinoth Kumar, K.; Sheeba Rani, S.; Radhakrishnan, G. (International Journal of Engineering and Technology, 2018)
The switching frequency of the bidirectional DC-DC converter is increased to make the size of the converter compact. This in turn results in higher switching losses. In order to overcome this drawback, a novel isolated bidirectional dc-dc converter (IBDC) is proposed. This work discuss about the performance of proposed IBDC. The performance of the proposed converter is evaluated using MATLAB /SIMULINK and the simulation results is verified with experimental results.Â Â